Recycling of Road Pavements – an Environmental Problem? Recycling von Strassenbelägen – ein Umweltproblem? - Martin Hugener; Peter Mattrel; Peter Schmid; Hermann W. Fritz (CHIMIA, 1998)
For several decades, in addition to bitumen, binders containing tar were used for road pavements in Switzerland. As tar contains up to 10000 times higher concentrations of toxic phenols and polycyclic aromatic hydrocarbons (PAH) than bitumen, tar was banned as a binder in road constructions. Nevertheless, several thousand tons of tar are still present in old pavements presenting a problem when roads have to be renovated. In 1997, regulations were introduced in Switzerland prohibiting the recycling of road materials with a content above 5000 mg PAH/kg binder.For the determination of PAH, several analytical methods are used ranging from simple screening tests to sophisticated analytical methods. Due to easy handling and simple instrumentation, thin-layer chromatography (TLC) is an adequate choice for road laboratories, whereas the determination of the quantitative composition of PAH mixtures has to be based on more demanding methods such as HPLC with fluorescence detection or GC-MS.